TYPES OF TAX DISPUTES - Golts, Edgars (Administrative and Criminal Justice, 2017)
This Work is a part of Author`s Promotion Work Study in the framework of evidences in tax legislation. Author has only set a goal to classify tax disputes by clearly understandable criteria. Author comes to the conclusion that tax disputes are divided into two groups, one of which, in turn, is divided into two subgroups. Author classifies tax disputes into law applied and legal relationship subjects. Author`s work reflects variety of scientific methods. Author provides subjects of involved tax disputes and definitions. The author classifies tax disputes by entities, involved in them, dividing in three pairs. In a wider scope, Author examines types of disputes between a tax authority and a taxpayer, Author classifies these disputes with regard to legal provisions used in solving relationships. They shall be divided in two groups. One group includes disputes arising of the interpretation of legal norms, and the second includes disputes arising from the violation of norms. The author divides the second group in two sub-groups - administrative offenses and criminal offenses.